Influence of Minimum Energy and Protein Levels in the Diet on Growth, Yield, and Meat Quality of Sin Cheng Duck Raised for Meat at 1-12 Weeks of Age - Ha, Nguyen Manh; My, Nguyen Thi Thuy; Ut, Nguyen Thi; Huong, Phan Thu; Xuan, Ngo Thanh (RA Journal Of Applied Research, 2023)
Research evaluating the effect of energy levels and minimum dietary protein on growth, performance, and meat quality of Sin Cheng ducks reared for meat at 1-12 weeks of age to find out energy and minimal protein levels for raising Sin Cheng ducks. The study was conducted on 450 Sin Cheng ducks from 1 day old to 12 weeks old arranged in 3 groups with different levels of protein and energy in the diet, corresponding to 3 age stages (0-3 weeks old)., 4-7 weeks old, 8-12 weeks old) respectively: Control group (DC): 2267 - 2329 - 2372Kcal, 17 - 15 - 14% protein; Experimental group one (TN1): 2533 – 2640 – 2711Kcal, 19 – 17 -16% protein; Experimental group two (TN2): 2001 - 2019 - 2033Kcal, 15 - 13 - 12% protein. Research results at week 12 showed that: With the energy and protein levels in the TN1 group giving the highest survival rate, the cumulative growth reached 2403.15 g/individual (duck), equivalent to the DC (2402.02 g/individual (duck) and higher than TN2 group (2303.03 g/individual). The percentage of carcass, breast, and thigh meat in the DC (69.73%, 16.62%, and 14.14%, respectively) was similar to that of the TN1 group (70.00%, 16.64% and 14.13% respectively) and much higher than TN2 group (66.3%, 15.62%, and 13.23%, respectively). The percentage of dry matter and protein in Sin Cheng duck’s breast meat and thigh meat in the DC and TN1 groups was similar and significantly higher than in the TN2 group. The energy and protein levels in the TN1 group (2533 – 2640 – 2711Kcal, 19 – 17 -16%) are the minimum energy and protein levels suitable for raising Sin Cheng ducks.